Pengaruh Fasilitas, Promosi dan Kualitas Pelayanan Terhadap Keputusan Pemakaian Jasa Pada Patra Jasa Convention Hotel Semarang - Kristitanti, Arisa; Pradhanawati, Ari; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2015)
Facilities, promotion and service quality influence the service usage decision. Convention Hotel Patra Jasa in Semarang get customer complaints about facilities, promotion, and service quality.The problems affect the service usage decision,it can be seen from the data of usage amount of rooms that fell as much as 21% and occupancy of the target is not realized in 2014.The purpose of this study was to determine the effect of facilities, promotion and service quality of the service usage decision. Type of research is explanatory research with collecting data with questionnaires and interviews. Sample in this research were 100 customers of Convention Hotel Patra Jasa in Semarang determined by purposive sampling technique. Data analysis that used in this study is simple linear regression, multiple linear regression, correlation analysis, t and f test.Based on this research, facilities has an effect on the service usage decision, promotion has an effect on the service usage decision and service quality has an effect on the service usage decision. Simultaneously only service quality has an effect on the use of decision services.The conclusion of this study showed that the facilities, promotion and service quality affect service usage decision partially, but simultaneously only Â service quality affect the service usage decision. The recommendations of this study are providing facilities more complete with other added facilities for guest room. Convention hotel Patra Jasa also must add media advertising to promote the hotel to public with attractive advertising messages. In addition, Convention hotel Patra Jasa should serve hotel guests quickly and understand their needs.